A Comprehensive Review of PV Driven Electrical Motors. (1st January 2020) - Narendra, A.; Venkataramana Naik, N.; Panda, Anup Kumar; Tiwary, Nishit
Abstract: As exponential usage in the consumption of energy sources, the world is searching for new energy sources. Hence, the energy crisis is a major dominant problem facing the world. The power generation using fossil fuel may extinct soon due to its reduction on day by day. Moreover, power generation using fossil fuels not only causing a greater part of the pollution but also unbalance in eco-system. Thus, renewable energy sources are a prominent solution to the energy crisis of the world as well as it is eco-friendly and pollution-free. Conversely, solar is one of the well-known and abundant energy sources and is widely used for direct electric power generation due to vast development in solar photovoltaic (PV) panel technology. PV fed motor drive based applications in a domestic, agricultural and industrial level increased. This work focus classification and control techniques of drive based on types of conversion stages. However, more emphasis on various converters, maximum power point tracking (MPPT) algorithms, pulse width modulation (PWM) techniques, inverter configurations, and drives are described as well as the choice of the configuration can be selected based on the requirements.